Effects of β-Mannanase Alone or Combined with Multi-Carbohydrase Complex in Corn–Soybean Meal Diets on Nutrient Metabolism and Gut Health of Growing Pigs - Gabriela Miotto Galli; Ines Andretta; Camila Lopes Carvalho; Thais B. Stefanello; Bruna Souza de Lima Cony; Alícia Zem Fraga; Karine Ludwig Takeuti; Aline Beatriz da Rosa; Marcos Kipper (Animals)
(1) Background: This study was performed to evaluate whether the addition of β-mannanase alone or combined with a multi-carbohydrase complex can improve diet digestibility, nutrient and energy metabolism, and the gut health of growing pigs. (2) Methods: Twenty-four pigs (35.56 ± 3.81 kg) were fed a control corn–soybean meal-based diet (no addition) or a control diet with β-mannanase (BM; 300 g/ton) or control diet β-mannanase plus a multi-carbohydrase complex including xylanase, β-glucanase, and arabinofuranosidases (BM + MCC; 300 + 50 g/ton) for 13 days. Total fecal and urine samples were collected from days 6 to 12. The feces samples were collected from all the pigs to determine fecal biomarkers using commercial ELISA tests. Blood samples were collected from all the pigs on day 13 to assess the serum concentrations of acute-phase proteins. All the pigs were euthanized on day 13 for intestinal tissue collection for morphometric analysis. Data were submitted to variance analysis and differences were considered significant at p ≤ 0.05 and a trend for 0.05 < p ≤ 0.10. (3) Results: The addition of BM and BM + MCC resulted in greater dry matter, protein, and energy digestibility coefficients, and protein (2.87% and 2.60%) and energy (2.61% and 1.44%) metabolizability coefficients compared to control (p < 0.05). A greater retention of nitrogen ratio and lower fecal energy were observed in BM and BM + MCC than in the control (p < 0.01). Furthermore, the addition of BM and BM + MCC resulted in lower manure production (29.78 and 49.77%, respectively) and fecal moisture (p < 0.001) compared to the control. The BM addition resulted in a greater villus area and villi height to crypt depth ratio compared to the control (p < 0.05). The addition of BM and BM + MCC diets also reduced the fecal calprotectin levels by 52 and 56% in relation to the control pigs. (4) Conclusions: The use of β-mannanase alone or associated with multi-carbohydrase complex improved nutritional digestibility, nutrient and energy metabolism, and gut health, and reduced the manure production of growing pigs.